Explosive plantar flexor performance: a comparison of elite sprinters versus physically active individuals - Crotty, E. D.; Furlong, L.-A.; Harrison, A. J. (ISBS Proceedings Archive (Michigan), 2021)
This study examined differences in explosive muscular torque production of the plantar flexors of participants with differing training backgrounds. Explosive performance of a group of elite sprinters (n = 14) and physically active individuals (n = 14) were examined during explosive and maximal isometric contractions across different muscle-tendon unit (MTU) lengths. The rate of torque development (RTD) across time windows (0-50, 50-100, 100-150 ms) and maximal voluntary torque (MVT) was measured. Sprinters exhibited greater early phase RTD (0-50, 50-100 ms) across MTU lengths. Relative MVT was greater for sprinters at the dorsiflexed MTU length only. The results suggest sprint-specific training contributes to the improved explosive performance of the plantar flexors across MTU lengths, particularly in the early phase of muscular contraction.